The Impact of Heterosexual Scripts on Women's Sexual Desire in Relationships. - Smets, Joëlle Wilhelmine; Miller, Sarah; Leys, Christophe (Archives of Sexual Behavior, 2025)
Numerous studies have described that women's sexual desire is lower than men's desire. Within a heterosexual couple, a sexual desire discrepancy can be associated with sexual and relationship dissatisfaction. The factors that negatively influence women's sexual desire are biological, psychological, relational, cognitive and sociocultural. The present study aimed to determine the extent to which adherence to sexual norms predicted sexual desire in women engaged in a romantic relationship (min. 6 months). These norms were addressed by Simon and Gagnon's (1984) notion of sexual scripts, which designate the sociocultural norms governing the sexual behaviors of men and women. A sample of women (N = 829, M age = 32 years, SD = 12.20, range = 18–72) completed a questionnaire about sexual desire and heterosexual scripts. The results showed that the more women in relationships say they felt desire, the less they subscribed to heterosexual scripts and particularly the conception that a man's sex drive is higher than a woman's. This conception seems to be the most determinant of women's sexual desire in relationships. The results attest also to the persistence and strength of heterosexual scripts which, despite greater equality between men and women, continue to negatively influence women's sexual desire. By becoming aware of these conditionings, women suffering from low sexual desire and sexual desire discrepancy within their couple can break free from them and experience a more fulfilling sexuality. Lastly, some interesting contradictory results are addressed in discussion.